2016
DOI: 10.4067/s0717-92002016000300012
|View full text |Cite
|
Sign up to set email alerts
|

Perfil lignoídico del tegumento de semillas de Araucaria angustifolia

Abstract: SUMMARYThe aim of this research was to quantify and identify the types of lignin and characterize its functionalization based on apparent physical resistance in each seed coat layers of Araucaria angustifolia. Each seed layer (exotesta, mesotesta and endotesta) was milled, homogenized and pre-extracted with solvents: cyclohexane, ethyl acetate and methanol for quantification of lignin. Pre-treatment with NaOH 1% was also performed in each layer of the seed for lignin quantification and for infrared spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Lignin present at plant cell walls can exhibit autofluorescence under UV or visible excitation (Donaldson & Radotic, 2013). Sampaio, Abreu, Augusto, Silva, and Ibanez (2016) observed lignin autofluorescence in araucaria seed integument, allowing identification of macrosclereids highly lignified at the exotestal by using a green excitation filter (330-385 nm).…”
Section: Genotypesmentioning
confidence: 97%
“…Lignin present at plant cell walls can exhibit autofluorescence under UV or visible excitation (Donaldson & Radotic, 2013). Sampaio, Abreu, Augusto, Silva, and Ibanez (2016) observed lignin autofluorescence in araucaria seed integument, allowing identification of macrosclereids highly lignified at the exotestal by using a green excitation filter (330-385 nm).…”
Section: Genotypesmentioning
confidence: 97%
“…As principais partes do pinhão são casca, endosperma e embrião. A casca, por sua vez, apresenta ainda partes denominadas exotesta, mesotesta e endotesta (Sampaio et al, 2016). Sua casca, geralmente descartada, possui teores significativos de compostos fenólicos e atividade antioxidante notável (Freitas et al, 2018) e potencial para aplicações em aerossóis, embalagens ativas e biodegradáveis (Fonseca et al, 2021;Souza et al, 2020).…”
Section: Introductionunclassified
“…The pinhão is a recalcitrant seed (Silva et al, 2011;Peralta et al, 2016). Sampaio et al (2016) described the pinhão seed coat consisting of three-layered: exotesta, mesotesta, and endotesta. Doni et al (1985) reported that the presence of the external coat delays the germination process of the Pinhão, likely due to the restriction to water inflow (Borges et al, 1987).…”
Section: Introductionmentioning
confidence: 99%